Identification and characterization of Clostridium sordellii toxin gene regulator - Sirigi Reddy, Apoorva Reddy (Kansas State University, 2014)
Toxigenic Clostridium sordellii causes uncommon but highly lethal infections in humans and animals. Recently, an increased incidence of C. sordellii infections has been reported in women undergoing obstetric interventions. Pathogenic strains of C. sordellii produce numerous virulence factors, including sordellilysin, phospholipase, neuraminidase, and two large clostridial glucosylating toxins, TcsL and TcsH. Recent studies have demonstrated that TcsL toxin is an essential virulence factor for the pathogenicity of C. sordellii. In this study, we identified and characterized TcsR as the toxin gene (tcsL) regulator in C. sordellii. High-throughput sequencing of two C. sordellii strains revealed that tcsR lies within a genomic region that encodes TcsL, TcsH, and TcsE, a putative holin. By using ClosTron technology, we inactivated the tcsR gene in strain ATCC 9714. Toxin production and tcsL transcription were decreased in the tcsR mutant strain. However, the complemented tcsR mutant produced large amounts of toxins, similar to the parental strain. Expression of the Clostridium difficile toxin gene regulator tcdR also restored toxin production to the C. sordellii tcsR mutant, showing that these sigma factors are functionally interchangeable.
Keywords: Clostridium sordellii; Toxin gene regulator; TcsR; Apoorva Reddy; Sirigi Reddy; Revathi Govind; Biology (0306); Microbiology (0410)